Evaluation of Random Amplified Polymorphic DNA and Simple Sequence Repeat markers in Moringa oleifera (Lam.) to establish population diversity - Vorster, Barend Juan (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2013.